Evaluation of a multiplex gastrointestinal PCR panel for the aetiological diagnosis of infectious diarrhoea. Issue 2 (1st February 2020) - Leli, Christian; Di Matteo, Luigi; Gotta, Franca; Vay, Daria; Cavallo, Valeria; Mazzeo, Roberta; Busso, Simone; Carrabba, Laura; Rocchetti, Andrea
Abstract: Background: Infectious diarrhoea is a significant cause of morbidity worldwide. Culture and microscopy are time-consuming and have a low yield. New rapid molecular methods such as multiplex PCR, have been recently introduced for aetiological diagnosis. Aim of this study was to compare the diagnostic yield of the FilmArray gastrointestinal panel with that of standard culture for aetiological diagnosis of infectious diarrhoea. Methods: We performed a retrospective analysis of results of stool samples already processed as part of routine clinical care in the interval from March 2016 to March 2019. Results: One hundred and eighty-three stool samples from as many patients were both cultured and tested by FilmArray and the comparison of diagnostic accuracy between culture and FilmArray with respect to Campylobacter spp., Salmonella spp., Shigella spp., Yersinia enterocolitica and Shiga-like toxin producing E. coli O157 gave the following results: 100% (95% confidence interval (CI): 85–100%) sensitivity; 93.4% (95% CI: 87.9–96.6%) specificity; 74.3% (95% CI: 57.5–86.4%) positive predictive value; 100% (95% CI: 96.7–100%) negative predictive value; 2.9 (95% CI: 1.6–5.1) positive likelihood ratio; zero negative likelihood ratio. By means of FilmArray gastrointestinal (GI) panel, we could identify 34.5% more pathogens ( p = .001). Bacteria were mostly detected in patients with 6 or more years of age ( χ 2 =17.1; p = .009) during summer. Conclusions: FilmArray GI panel showed a very good diagnostic performance compared to culture for diagnosis of infectious diarrhoea and gave a more detailed picture of the spectrum of the pathogens involved.